2022
DOI: 10.1186/s42523-022-00172-1
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial communities in the gastrointestinal tract segments of helminth-resistant and helminth-susceptible sheep

Abstract: Background Helminth parasitism is a world-wide problem in livestock industries, with major impacts on health, welfare and productivity. The role of the gut microbiota in host-helminth interactions in ruminants has been extensively examined and the present study added to this body of knowledge by assessing the effects of resistance and susceptibility to helminth infection in the gastro-intestinal tract (GIT). Australian Sheep Breeding Values (ASBVs) for faecal egg count (FEC) were used to select… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 58 publications
(40 reference statements)
1
4
0
Order By: Relevance
“…Finally, Parabacteroides , Prevotella , and Butyrivibrio were associated with salmonellosis, EPEC, and helminth infections. Of note, similar observations have been reported previously, both from epidemiological assessments and experimental veterinary medical assessments [ 61 , 62 , 63 , 64 , 65 ]. Such coincidences in the literature confirm the findings of the assessments presented here, although potential causal relations are still largely unknown.…”
Section: Discussionsupporting
confidence: 87%
“…Finally, Parabacteroides , Prevotella , and Butyrivibrio were associated with salmonellosis, EPEC, and helminth infections. Of note, similar observations have been reported previously, both from epidemiological assessments and experimental veterinary medical assessments [ 61 , 62 , 63 , 64 , 65 ]. Such coincidences in the literature confirm the findings of the assessments presented here, although potential causal relations are still largely unknown.…”
Section: Discussionsupporting
confidence: 87%
“…However, taking into account that there is no direct evidence that MNP may have some activity against mycoplasma, we can hypothesize that the lack of parasites may prevent abomasum colonization by microbes of the Mycoplasmataceae family. In this sense, Paz et al, (2022) [ 38 ] reported that the whole GI tract of sheep with low epg counts had lower Mycoplasma abundance than sheep with high epg counts. The use of a limited number of animals is a constraint of the experimental design used in this research.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike Mycoplasmataceae , the family Methanobacteriaceae , whose relative abundance in sheep abomasum was 1.89, was increased in 3 out of 5 dewormed animals. Considering that methanobacteria are usually identified in the rumen but not in the abomasum of sheep [ 38 ], we believe that this family isolated from the abomasum would actually come down from the rumen of treated sheep. Methanobacteria can pass from the rumen to the abomasum in sheep through a narrow passage called the reticulum-omasal orifice; this passage is normally closed, but it can open to allow food and fluid to pass from the rumen to the abomasum [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Oscillibacter is a common genus in herbivores and may assist in plant polysaccharide utilization [ 16 ], was identified on day 0. Some articles showed that Oscillibacter contained beneficial bacteria, of which the metabolites like butyric acid and alpha-linolenic acid can resist inflammation and protect intestinal mucosa [ 29 , 30 ]. Speculating effects of ivermectin on these genera may affect the intestinal microbiota balance and change the fiber metabolism, which reduces the protective function of normal microbiota.…”
Section: Discussionmentioning
confidence: 99%